1991
DOI: 10.1542/peds.88.5.1031
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Responses to Influenza B Viruses in Immunologically Unprimed Children

Abstract: The cocirculation in several parts of the world of influenza viruses B/Yamagata/16/88 and B/Victoria/2/87, which are genetically and antigenically divergent, has prompted the question of whether immunization with one viral antigen is sufficient for protection against both strains. Twenty-three high-risk infants and young children were immunized with a commercial trivalent influenza vaccine containing the antigens of influenza virus B/Yamagata/16/88. When antibodies against influenza viruses B/Yamagata/16/88 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Multiplexed Immunoassays for Influenza Virus Detection and Differentiation. It has been reported that the two lineages of influenza B viruses are so different antigenically that vaccination with strains from one lineage may not provide good protection against infection with strains from another lineage . Since influenza virus vaccines are currently formulated to include only a single strain of influenza B virus, this lack of antigenic cross-reactivity has made the designation of a type B vaccine strain problematic in seasons when viruses of both lineages circulate.…”
Section: Resultsmentioning
confidence: 99%
“…Multiplexed Immunoassays for Influenza Virus Detection and Differentiation. It has been reported that the two lineages of influenza B viruses are so different antigenically that vaccination with strains from one lineage may not provide good protection against infection with strains from another lineage . Since influenza virus vaccines are currently formulated to include only a single strain of influenza B virus, this lack of antigenic cross-reactivity has made the designation of a type B vaccine strain problematic in seasons when viruses of both lineages circulate.…”
Section: Resultsmentioning
confidence: 99%
“…Determining how initial exposure to one strain of influenza B virus impacts subsequent responses to future strains may be a key factor to consider when testing next-generation influenza vaccines, especially in children who may only have been exposed to an IBV strain from one lineage prior to vaccination. Other studies for example have shown that children vaccinated with a trivalent influenza vaccine (TIV) containing a B/YAM antigen elicited cross-reactive antibody responses against B/VIC viruses if they were previously immunized to B/VIC, but not if they were unexposed 35 . Data on B/VIC vaccinations in children with no pre-existing immunity to IBV is scarce, however children vaccinated with B/VIC based vaccines were shown to have low immune responses to B/VIC antigens when these children were primed with B/YAM the previous season 36 .…”
Section: Discussionmentioning
confidence: 99%
“…I NACI concludes that there is insufficient evidence (in either quantity and/or quality) to make a recommendation, however other factors may influence decision-making. * General design specific criteria are outlined in Harris et al, 2001 4 .…”
Section: Poormentioning
confidence: 99%